PENGARUH KOMBINASI PUPUK AB MIX DAN PUPUK ORGANIK CAIR AZOLLA MICROPHYLLA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG (IPOMEA REPTANSPOIR) PADA BUDIDAYA HIDROPONIK RAKIT APUNG - Kusumaningsih, Fitri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Water spinach (Ipomea reptans Poir) is a vegetable plant that is a source of nutrients. Efforts to increase water spinach production are important, including hydroponic cultivation to anticipate land limitations. Floating raft hydroponics is an implemented cultivation technique. The combination of AB Mix and liquid organic fertilizer (POC) Azolla microphylla is thought to increase the growth and yield of water spinach. The purpose of this study was to determine the POC content of Azolla microphylla and to determine the effect of the combination of AB Mix and POC Azolla microphylla on the performance, growth and yield of water spinach. This study consisted of a quantitative descriptive study of the content of Azolla microphylla and the performance of water spinach plants with parameters of lateral roots, axillary branches, and leaf color followed by experimental research using Completely Randomized Design (CRD) with P0 treatment (AB Mix 0% + POC 0%), P1 (AB Mix 75% + POC 25%), P2 (AB Mix 50% + POC 50%), P3 (AB Mix 25% + POC 75%), P4 (POC 100%), P5 (AB Mix 100%) in three replicates. Parameters observed were growth (plant height, number of leaves, leaf area, chlorophyll content) and yield (total wet weight of plants). The data analysis technique used descriptive analysis and analysis of variance (Anova) and continued with Duncan's Distance Test (UJD) with a significance of 5%. The results of this study showed that the POC content of Azolla microphylla N was 0.560%, P2O5 was 2.44%, K2O was 0.19%. The results of Anova showed that there was an effect of the combination of AB Mix fertilizer and Azolla microphylla POC on the performance of water spinach plants including lateral roots, axillary branches, and leaf color. The results of the Anova test showed that the combination treatment of AB Mix and POC Azolla microphylla affected the growth and yield of water spinach plants on the parameters of plant height, number of leaves, leaf area, chlorophyll content and total wet weight of water spinach plants. The most effective combination of AB Mix and POC Azolla microphylla fertilizers on the growth and yield and performance of kale was P1 treatment (75% AB Mix + 25% POC Azolla microphylla).